Infection with Jujube Witches’ Broom Phytoplasma Alters the Expression Pattern of the Argonaute Gene Family in Ziziphus jujuba - Jia Yao; Zesen Qiao; Ziming Jiang; Xueru Zhao; Ziyang You; Wenzhe Zhang; Jiancan Feng; Chenrui Gong; Jidong Li (Microorganisms)
The cultivation of jujube (Ziziphus jujuba) in China is threatened by jujube witches’ broom (JWB) disease, a devastating infectious disease associated with JWB phytoplasma (‘Candidatus Phytoplasma ziziphi’). In many plants, proteins in the Argonaute (AGO) family, as main components of the RNA-induced silencing complex (RISC), play important roles in RNA silencing and pathogen resistance. The jujube telomere-to-telomere genome was searched by BLAST using Arabidopsis AGOs as probes. A total of nine jujube AGO gene members were identified, with each containing the conserved N-terminal, PZA, and PIWI domains. Phylogenetic analysis revealed that the nine jujube AGOs scattered into all three Arabidopsis AGO clades. Expression patterns of the ZjAGO genes were analyzed in response to phytoplasma in transcriptome data and by qRT–PCR. The jujube–phytoplasma interaction altered the expression of jujube AGO genes. ZjAGO1 and ZjAGO8 were up-regulated in the majority of the eight sampling periods subjected to qRT–PCR analysis. In the transcriptome data, ZjAGO1 and ZjAGO8 were also up-regulated during the key stages 37 and 39 weeks after grafting (WAG) with phytoplasma-infected material. These two jujube Argonaute genes may play important roles in response to JWB phytoplasma infection.